Optimizing Glycemic Control through Multidisciplinary Care: A Case of Type 2 Diabetes Mellitus with Foot Ulceration - Akhmad Kheru; Novi Amin Juraini; Khaula Azzahra Muslihah Dien; Kirana Dwi Rahayu; Komang Angel Ayudya; Laeli Resti Oktapiani; Lattifah Anggun; Yuri Nurdiantami (CV. FOUNDAE, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by impaired insulin secretion or resistance, which frequently remains undiagnosed until complications develop, and persistent hyperglycemia contributes to multisystem damage, particularly involving vascular, neural, renal, and integumentary systems, with major risk factors including family history, obesity, unhealthy dietary patterns, and physical inactivity; in this context, a 63-year-old woman presented with blistering lesions on the left hallux accompanied by swelling, pain, and paresthesia, with a medical history of hypertension, irregular eating habits, insufficient physical activity, and a familial predisposition to diabetes, while physical examination revealed a body mass index of 26.84 kg/m² with stable vital signs, and random blood glucose was 328 mg/dL, confirming severe hyperglycemia and establishing the diagnosis of T2DM, for which management encompassed pharmacological therapy (metformin, glimepiride, amlodipine, antibiotics, analgesics), patient education, psychosocial support, and lifestyle modification, and following comprehensive intervention the patient demonstrated improved disease awareness, enhanced family support, and better adherence to lifestyle changes, with outcomes emphasizing stabilization of glycemic levels, prevention of further complications, and improvement in overall quality of life, thereby underscoring the significance of a multidisciplinary approach in T2DM management that integrates medical therapy, education, psychosocial support, and behavioral as well as environmental modifications, and highlighting that such comprehensive strategies are essential to achieve optimal glycemic control and reduce the risk of long-term complications, while also illustrating the clinical relevance of early detection and holistic intervention in patients with diabetes who present with foot lesions, since these manifestations often indicate advanced disease progression and require coordinated care to prevent disability and improve prognosis, and ultimately this case contributes to the growing evidence that effective diabetes management must extend beyond pharmacological treatment to encompass patient-centered education, psychosocial reinforcement, and lifestyle restructuring, thereby offering a model of integrated care that can be applied more broadly in clinical practice to enhance outcomes in individuals living with T2DM.